Phosphorus negative electrode material and preparation method thereof
By adding ultra-thin Na/Na3P/C composite foil to the surface of the phosphorus/carbon composite electrode, the problem of low energy density of sodium ion batteries is solved, and the effect of improving the primary reversible specific capacity and energy density is achieved.
Patent Information
- Application Number
- CN202411565209.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The energy density of existing sodium ion batteries is less than 150 Wh kg−1, mainly due to the low theoretical specific capacity of hard carbon anode and the large volume change of phosphorus anode material during charging/discharging, resulting in serious loss of initial irreversible capacity.
By adding a layer of ultra-thin sodium metal composite foil with controllable thickness to the surface of the original high-capacity phosphorus/carbon composite electrode, the pre-sodiumization of the ultra-thin Na/Na3P/C composite foil is used to compensate for the initial irreversibility of the phosphorus/carbon composite electrode. Capacity loss.
It effectively improves the initial reversible specific capacity of the phosphorus negative electrode, increases the energy density of the sodium ion battery, and simplifies the sodium compensation operation, avoiding the deficiency of additive doping pre-sodiumization and metal sodium contact pre-sodiumization.
Smart Images

Figure CN119480920A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high specific energy batteries, and in particular relates to a phosphorus negative electrode material and a preparation method thereof. Background Art Currently, lithium-ion batteries are widely used in battery products, electric vehicles, grid storage and other fields and show great market prospects. Unfortunately, the shortage and uneven distribution of lithium resources hinder the large-scale application of lithium ions (such as grid energy storage). Sodium resources are abundant, and the similar physical and chemical properties to lithium allow the development of sodium-ion batteries to adopt or draw on the technology of lithium-ion batteries. Therefore, sodium-ion batteries are widely regarded as an important direction for the development of next-generation electrochemical energy storage devices. However, due to the theoretical specific capacity of hard carbon negative electrodes is less than 300 mAh g −1 Therefore, the energy density of current commercial sodium-ion batteries is less than 150 Wh kg −1 , which is about half of that of lithium-ion batteries, which greatly hinders its application. Therefore, the research on high specific capacity negative electrode materials is the key to the development of sodium-ion batteries.
[0002] The theoretical specific capacity of phosphorus anode for sodium storage is the highest among all candidate materials, reaching 2596 mAh g −1 , is an ideal choice for high-energy sodium-ion battery anode materials. However, the huge volume change of phosphorus-based anode materials during charge / discharge requires them to be made into nanostructures or composited with carbon materials with large specific surface areas. Although the cycle stability is improved, the active sites they provide inevitably increase the irreversible loss of sodium during the first cycle.
[0003] Therefore, how to improve the initial reversible specific capacity is crucial to the development of phosphorus negative electrodes and the improvement of the energy density of sodium-ion batteries. Pre-sodiumization (sodium compensation) is a technology that pre-places sodium foil or sodium-rich materials on the electrode surface to supplement the irreversible sodium loss of the battery in the first cycle. It provides an effective solution to reduce the irreversible capacity loss in sodium-ion batteries. Pre-sodiumization technology can be divided into four categories: additive doping pre-sodiumization, electrochemical pre-sodiumization, chemical pre-sodiumization and metallic sodium contact pre-lithiation. After the sodium is added, some inactive substances will remain on the electrode surface, which will affect the performance of the battery. In addition, most of these pre-sodium materials are highly active and have poor air stability.
[0004] Electrochemical pre-sodiumization usually requires the battery to be disassembled and reassembled, the required equipment is complex, and the operating environment requirements are strict, which reduces the applicability of this technology in commercial battery manufacturing.
[0005] The pre-sodiumization agent used in chemical pre-sodiumization is often highly reactive and needs to be carried out under an inert atmosphere. The electrode material after sodiumization also has a certain reactivity and the material is in a metastable state. During the subsequent slurry mixing and coating process, the electrode sheet is very easy to absorb water or react with other additives, which is not conducive to battery processing.
[0006] Sodium foil contact pre-sodiumization uses metallic sodium foil as a pre-sodiumization agent. After the pre-sodiumization is completed, the excess sodium foil needs to be removed and the amount of sodium compensation is difficult to achieve precise control. Summary of the invention
[0007] The present invention provides a phosphorus negative electrode material and a preparation method thereof, which is achieved by adding a layer of ultra-thin sodium metal composite foil with controllable thickness on the surface of the original high-capacity phosphorus / carbon composite electrode, that is, the pre-sodiumization effect of the ultra-thin sodium metal composite foil is combined with the phosphorus / carbon composite electrode with high initial irreversible capacity to construct a new phosphorus negative electrode material. The added composite foil acts as a pre-sodiumization agent to supplement the capacity loss (initial irreversible capacity) caused by the initial irreversible reaction of the original phosphorus / carbon composite electrode. By controlling the thickness of the composite foil, it is possible to complete the pre-sodiumization without removing excess sodium foil, and the whole is a new phosphorus negative electrode material.
[0008] The present invention provides a method for preparing a phosphorus negative electrode material, comprising the following steps: 1) preparing the first phosphorus / carbon composite material into an electrode, and testing the initial irreversible capacity of the electrode; 2) placing the second phosphorus / carbon composite material between at least two layers of sodium metal foil, and preparing an ultrathin Na / Na3P / C composite foil by repeated mechanical rolling and folding, so that the capacity of the obtained ultrathin Na / Na3P / C composite foil is equivalent to the initial irreversible capacity of the electrode prepared from the first phosphorus / carbon composite material obtained in step 1); 3) The ultra-thin Na / Na3P / C composite foil obtained in step 2) is directly covered on the surface of the first phosphorus / carbon composite material to form a high reversible capacity phosphorus negative electrode material.
[0009] Furthermore, in step 2), the amount of the second phosphorus / carbon composite material added is 5-25% of the total mass of the ultra-thin Na / Na3P / C composite foil.
[0010] Furthermore, in step 2), the amount of the second phosphorus / carbon composite material added accounts for 15% of the total mass of the ultra-thin Na / Na3P / C composite foil. Furthermore, in step 2), the specific thickness of the ultra-thin Na / Na3P / C composite foil is 5-30 μm.
[0011] Furthermore, in step 2), the specific thickness of the ultra-thin Na / Na3P / C composite foil is 15 μm.
[0012] Furthermore, the phosphorus in the first phosphorus / carbon composite material or the second phosphorus / carbon composite material includes at least one of red phosphorus, black phosphorus, yellow phosphorus, and purple phosphorus; the carbon includes at least one of hard carbon, amorphous carbon, graphene sheets, redox graphene sheets, biomass carbon, and carbon nanotubes.
[0013] Furthermore, the mass content of carbon in the first phosphorus / carbon composite material is 1-50%.
[0014] Furthermore, the mass content of carbon in the second phosphorus / carbon composite material is 1-24%.
[0015] The present invention also proposes a phosphorus negative electrode material prepared by any of the above preparation methods.
[0016] The present invention has the following advantages: The present invention uses an ultra-thin Na / Na3P / C composite foil as a pre-sodiumization material for a phosphorus negative electrode. First, a second phosphorus / carbon composite material and a metal sodium foil are repeatedly mechanically rolled and folded, wherein phosphorus reacts with metal sodium to generate Na3P, thereby enhancing the machinability of sodium and preparing a low-capacity ultra-thin Na / Na3P / C composite foil. Then, the ultra-thin Na / Na3P / C composite foil is used to perform sodium compensation on the first phosphorus / carbon composite material, i.e., the phosphorus negative electrode. The residue is a fast ion conductor Na3P and slightly sodiumized carbon, which not only does not affect the performance of the battery, but also helps to improve the stability of the electrode interface. The ultra-thin Na / Na3P / C composite foil has the simplicity of sodium compensation operation for the phosphorus negative electrode and the side effects of the residue, effectively overcomes the deficiencies of additive doping pre-sodiumization and metal sodium contact pre-sodiumization, and improves the capacity of the sodium ion battery, thereby improving the energy density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings: Figure 1 This is the XRD spectrum of the phosphorus / carbon composite material obtained in Example 1 of the present invention.
[0018] Figure 2 This is the initial charge / discharge curve of the phosphorus / carbon negative electrode obtained in Example 1 of the present invention.
[0019] Figure 3 This is the XRD spectrum of the Na / Na3P / C composite foil obtained in Example 1 of the present invention.
[0020] Figure 4 These are digital photos of the Na / Na3P / C composite foil obtained in Example 1 of the present invention and the pure Na foil in Comparative Example 2.
[0021] Figure 5This is a curve showing complete removal of elemental sodium from the Na / Na3P / C composite foil obtained in Example 1 of the present invention.
[0022] Figure 6 This is a cycle diagram of the specific capacity of the Na / Na3P / C composite foil improved phosphorus / carbon negative electrode based battery obtained in Experimental Example 1 of the present invention. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. In the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.
[0024] The present invention provides a method for preparing a phosphorus negative electrode material, comprising the following steps: 1) preparing the first phosphorus / carbon composite material into an electrode, and testing the initial irreversible capacity of the electrode; 2) placing the second phosphorus / carbon composite material between at least two layers of sodium metal foil, and preparing an ultrathin Na / Na3P / C composite foil by repeated mechanical rolling and folding, so that the capacity of the obtained ultrathin Na / Na3P / C composite foil is equivalent to the initial irreversible capacity of the electrode prepared from the first phosphorus / carbon composite material obtained in step 1); 3) The ultra-thin Na / Na3P / C composite foil obtained in step 2) is directly covered on the surface of the first phosphorus / carbon composite material to form a high reversible capacity phosphorus negative electrode material.
[0025] The embodiment of the present invention uses an ultra-thin Na / Na3P / C composite foil as a pre-sodiumization material for the phosphorus negative electrode. First, the second phosphorus / carbon composite material and the metal sodium foil are repeatedly mechanically rolled and folded, wherein phosphorus reacts with metal sodium to generate Na3P, thereby enhancing the machinability of sodium and preparing a low-capacity ultra-thin Na / Na3P / C composite foil. Then, the ultra-thin Na / Na3P / C composite foil is used to perform sodium compensation on the first phosphorus / carbon composite material, i.e., the phosphorus negative electrode. The residue is a fast ion conductor Na3P and slightly sodiumized carbon, which not only does not affect the performance of the battery, but also helps to improve the stability of the electrode interface. The simplicity of the ultra-thin Na / Na3P / C composite foil for sodium compensation of the phosphorus negative electrode and the lack of side effects of the residue effectively overcome the deficiencies of additive doping pre-sodiumization and metal sodium contact pre-sodiumization, and improve the capacity of the sodium ion battery, thereby improving the energy density of the battery.
[0026] In step 1) of the embodiment of the present invention, the initial irreversible capacity of the first phosphorus / carbon composite material after being prepared into an electrode is tested to determine the amount of capacity to be compensated subsequently.
[0027] In step 2) of the embodiment of the present invention, mechanical rolling causes phosphorus to react with metallic sodium at the interface to form a fast ion conductor Na3P. As the number of rolling increases, phosphorus is completely converted to Na3P and is uniformly embedded in the Na block, thus obtaining a Na / Na3P / C composite foil. Na3P is uniformly distributed in the composite foil, so the initial amount of the second phosphorus / carbon composite material added has an important influence on the capacity of the composite foil, and the thickness of the composite foil is also proportional to the capacity.
[0028] In one embodiment of the present invention, in step 2), the content of Na3P and C in the Na / Na3P / C composite foil directly affects whether it can be prepared into an ultra-thin composite foil by mechanical rolling. Therefore, in order to ensure that a composite foil of the required thickness is obtained, the amount of the second phosphorus / carbon composite material added accounts for 5-25% of the total mass of the ultra-thin Na / Na3P / C composite foil. Preferably, in step 2), the amount of the second phosphorus / carbon composite material added accounts for 15% of the total mass of the ultra-thin Na / Na3P / C composite foil. In the embodiment of the present invention, different amounts of the second phosphorus / carbon composite material added have a certain effect on the capacity of the Na / Na3P / C composite foil. If the amount of the second phosphorus / carbon composite material added is too high, the metallic sodium will be completely reacted and unable to form a foil material. If the amount of the second phosphorus / carbon composite material added is too low, the metallic sodium will almost not react and cannot be pressed thin, so it is necessary to add an appropriate amount of the second phosphorus / carbon composite material.
[0029] In one embodiment of the present invention, in step 2), the specific thickness of the ultra-thin Na / Na3P / C composite foil is 5-30 μm; preferably, the specific thickness of the ultra-thin Na / Na3P / C composite foil is 15 μm. The thickness of the ultra-thin Na / Na3P / C composite foil has a certain influence on the composite foil. If the Na / Na3P / C composite foil is too thick, it will lead to excessive active sodium, and if the Na / Na3P / C composite foil is too thin, it will lead to insufficient active sodium.
[0030] Specifically, in step 1) and step 2), the first phosphorus / carbon composite material and the second phosphorus / carbon composite material are prepared by ball milling or chemical method. The phosphorus in the first phosphorus / carbon composite material or the second phosphorus / carbon composite material includes at least one of red phosphorus, black phosphorus, yellow phosphorus, and purple phosphorus; the carbon includes at least one of hard carbon, amorphous carbon, graphene sheet, redox graphene sheet, biomass carbon, and carbon nanotubes. The mass content of carbon in the first phosphorus / carbon composite material is 1-50%; the mass content of carbon in the second phosphorus / carbon composite material is 1-24%.
[0031] The embodiment of the present invention further provides a phosphorus negative electrode material prepared by any of the above-mentioned preparation methods.
[0032] The phosphorus negative electrode material proposed in the embodiment of the present invention uses a new electrode composed of an ultra-thin Na / Na3P / C composite foil and a high-capacity phosphorus / carbon negative electrode to effectively increase the energy density of the battery without side effects.
[0033] The present invention will be described in detail below with reference to embodiments and drawings.
[0034] Example 1 A method for preparing a phosphorus negative electrode material comprises the following steps: The first phosphorus / carbon composite material having a carbon mass content of 50% is prepared into an electrode, and its initial irreversible capacity loss is evaluated by charge / discharge; The second phosphorus / carbon composite material with a carbon mass content of 20% and metallic sodium are in a mass ratio of 15:85, and the phosphorus is completely converted into Na3P particles by repeated mechanical rolling and folding to prepare an ultra-thin Na / Na3P / C composite foil (about 20 μm), so that the capacity generated by the ultra-thin Na / Na3P / C composite foil is equivalent to the initial irreversible capacity (initial sodium loss) of the first red phosphorus / carbon composite material; The ultra-thin Na / Na3P / C composite foil is covered on the surface of the electrode prepared from the first phosphorus / carbon composite material to obtain a novel phosphorus / carbon composite negative electrode.
[0035] Figure 1 is the XRD pattern of the obtained phosphorus / carbon composite material. Figure 1 It can be seen that the phosphorus in the phosphorus / carbon composite material is an amorphous structure.
[0036] Figure 2 is the initial charge / discharge curve of phosphorus / carbon negative electrode. Figure 2 It can be obtained that the initial coulombic efficiency of the phosphorus / carbon composite electrode is 67.9%, that is, the initial irreversible capacity loss is 32.1%.
[0037] Figure 3 The XRD pattern of Na / Na3P / C composite foil is shown in Figure 2. Figure 3 It can be seen that the phosphorus in the second phosphorus / carbon composite material is completely converted into Na3P, and the Na / Na3P / C composite foil is composed of Na, Na3P and C.
[0038] Figure 4 (a) is a digital photo of Na / Na3P / C composite foil. Figure 4 (a) As can be seen, a 20 μm thick and complete Na / Na3P / C composite foil was successfully prepared.
[0039] Example 2 A method for preparing a phosphorus negative electrode material comprises the following steps: The first red phosphorus / carbon composite material containing 50% carbon was prepared into an electrode, and its initial irreversible capacity loss was evaluated by charge / discharge; The second red phosphorus / carbon composite material with a carbon content of 1% and metallic sodium are mixed in a mass ratio of 15:85, and the phosphorus is completely converted into Na3P particles by repeated mechanical rolling and folding to prepare an ultrathin Na / Na3P / C composite foil (about 25 μm), so that the capacity generated by the ultrathin Na / Na3P / C composite foil is equivalent to the initial irreversible capacity of the first red phosphorus / carbon composite material; The ultra-thin Na / Na3P / C composite foil is covered on the surface of the electrode prepared from the first red phosphorus / carbon composite material to obtain a modified phosphorus / carbon composite negative electrode.
[0040] Example 3 A method for preparing a phosphorus negative electrode material comprises the following steps: The first red phosphorus / carbon composite material containing 50% carbon was prepared into an electrode, and its initial irreversible capacity loss was evaluated by charge / discharge; The second red phosphorus / carbon composite material with a carbon content of 24% and metallic sodium are mixed in a mass ratio of 15:85, and the phosphorus is completely converted into Na3P particles by repeated mechanical rolling and folding to prepare an ultra-thin Na / Na3P / C composite foil (about 5 μm), so that the capacity generated by the ultra-thin Na / Na3P / C composite foil is equivalent to the initial irreversible capacity of the first red phosphorus / carbon composite material; The ultra-thin Na / Na3P / C composite foil is covered on the surface of the electrode prepared from the first red phosphorus / carbon composite material to obtain a modified phosphorus / carbon composite negative electrode. Example 4 A method for preparing a phosphorus negative electrode material comprises the following steps: The first red phosphorus / carbon composite material containing 10% carbon was prepared into an electrode, and its initial irreversible capacity loss was evaluated by charge / discharge; The second red phosphorus / carbon composite material with a carbon content of 24% and metallic sodium are mixed in a mass ratio of 15:85, and the phosphorus is completely converted into Na3P particles by repeated mechanical rolling and folding to prepare an ultrathin Na / Na3P / C composite foil (about 10 μm), so that the capacity generated by the ultrathin Na / Na3P / C composite foil is equivalent to the initial irreversible capacity of the first red phosphorus / carbon composite material; The ultra-thin Na / Na3P / C composite foil is covered on the surface of the electrode prepared from the first red phosphorus / carbon composite material to obtain a modified phosphorus / carbon composite negative electrode.
[0041] Example 5 A method for preparing a phosphorus negative electrode material comprises the following steps: The first red phosphorus / carbon composite material containing 10% carbon was prepared into an electrode, and its initial irreversible capacity was evaluated by charge / discharge; The second red phosphorus / carbon composite material with a carbon content of 1% and metallic sodium are mixed in a mass ratio of 15:85, and the phosphorus is completely converted into Na3P particles by repeated mechanical rolling and folding to prepare an ultra-thin Na / Na3P / C composite foil (about 15 μm), so that the capacity generated by the ultra-thin Na / Na3P / C composite foil is equivalent to the initial irreversible capacity of the first red phosphorus / carbon composite material; The ultra-thin Na / Na3P / C composite foil is covered on the surface of the electrode prepared from the first red phosphorus / carbon composite material to obtain a modified phosphorus / carbon composite negative electrode.
[0042] Example 6 A method for preparing a phosphorus negative electrode material comprises the following steps: The first red phosphorus / carbon composite material containing 50% carbon is prepared into an electrode, and its initial irreversible capacity is evaluated by charge / discharge; The second red phosphorus / carbon composite material with a carbon content of 10% and metallic sodium are mixed in a mass ratio of 5:95, and the phosphorus is completely converted into Na3P particles by repeated mechanical rolling and folding to prepare an ultrathin Na / Na3P / C composite foil (about 30 μm), so that the capacity generated by the ultrathin Na / Na3P / C composite foil is equivalent to the initial irreversible capacity of the first red phosphorus / carbon composite material; The ultra-thin Na / Na3P / C composite foil is covered on the surface of the electrode prepared from the first red phosphorus / carbon composite material to obtain a modified phosphorus / carbon composite negative electrode.
[0043] Example 7 A method for preparing a phosphorus negative electrode material comprises the following steps: The first red phosphorus / carbon composite material containing 50% carbon is prepared into an electrode, and its initial irreversible capacity is evaluated by charge / discharge; The second red phosphorus / carbon composite material with a carbon content of 10% and metallic sodium are mixed in a mass ratio of 25:75, and the phosphorus is completely converted into Na3P particles by repeated mechanical rolling and folding to prepare an ultrathin Na / Na3P / C composite foil (about 12 μm), so that the capacity generated by the ultrathin Na / Na3P / C composite foil is equivalent to the initial irreversible capacity of the first red phosphorus / carbon composite material; The ultra-thin Na / Na3P / C composite foil is covered on the surface of the electrode prepared from the first red phosphorus / carbon composite material to obtain a modified phosphorus / carbon composite negative electrode.
[0044] Comparative Example 1 A method for preparing a phosphorus negative electrode material comprises the following steps: A first red phosphorus / carbon composite material containing 50% carbon is prepared into an electrode.
[0045] Comparative Example 2 A method for preparing a phosphorus negative electrode material comprises the following steps: Metal sodium is placed on the surface of the first phosphorus / carbon composite material. Since metal sodium cannot be compressed thinly, it cannot be directly pressed onto the surface of the first phosphorus / carbon composite material.
[0046] Figure 4 (b) is a digital photo of pure Na foil. Figure 4 It can be seen that the 20 μm thick and complete Na / Na3P / C composite foil was successfully prepared in Example 1. However, the pure sodium foil adhered to the plastic bag after being rolled to 50 μm and could not be completely removed.
[0047] Test Example 1 (1) The Na / Na3P / C composite foil and metallic sodium obtained in Example 1 were used as electrodes to assemble a battery, so that the active sodium in the Na / Na3P / C composite foil was completely removed, and the content of active sodium in the Na / Na3P / C composite foil was determined. Figure 5 .Depend on Figure 5 It can be obtained that the capacity of Na / Na3P / C composite foil is about 625 mAh g −1 The 20μm Na / Na3P / C composite foil has a capacity of approximately 1.2 mAh.
[0048] (2) The phosphorus / carbon composite negative electrode obtained in Example 1 and the phosphorus / carbon composite electrode obtained in Comparative Example 1 were respectively matched with a sodium nickel iron manganese oxide positive electrode to assemble a full battery, and the battery was charged / discharged at a current density of 0.1 / 0.5C to test the electrochemical performance of the battery. Figure 6 . Figure 6 The cycle diagram of the specific capacity of the Na / Na3P / C composite foil improved phosphorus / carbon negative electrode based battery obtained in Example 1. Figure 6 It can be seen that the capacity of the new phosphorus / carbon composite material assembled battery formed by the Na / Na3P / C composite foil and the original first red phosphorus / carbon composite material in Comparative Example 1 is significantly improved compared with the original first red phosphorus / carbon composite material.
[0049] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a phosphorus negative electrode material, characterized in that: The steps include: 1) preparing the first phosphorus / carbon composite material into an electrode, and testing the initial irreversible capacity of the electrode; 2) placing the second phosphorus / carbon composite material between at least two layers of sodium metal foil, and preparing an ultrathin Na / Na3P / C composite foil by repeated mechanical rolling and folding, so that the capacity of the obtained ultrathin Na / Na3P / C composite foil is equivalent to the initial irreversible capacity of the electrode prepared from the first phosphorus / carbon composite material obtained in step 1); 3) The ultra-thin Na / Na3P / C composite foil obtained in step 2) is directly covered on the surface of the first phosphorus / carbon composite material to form a high reversible capacity phosphorus negative electrode material.
2. The preparation method according to claim 1, characterized in that: In step 2), the amount of the second phosphorus / carbon composite material added is 5-25% of the total mass of the ultra-thin Na / Na3P / C composite foil.
3. The preparation method according to claim 2, characterized in that: In step 2), the amount of the second phosphorus / carbon composite material added accounts for 15% of the total mass of the ultra-thin Na / Na3P / C composite foil.
4. The preparation method according to claim 1, characterized in that: In step 2), the specific thickness of the ultra-thin Na / Na3P / C composite foil is 5-30 μm.
5. The preparation method according to claim 4, characterized in that: In step 2), the specific thickness of the ultra-thin Na / Na3P / C composite foil is 15 μm.
6. The preparation method according to claim 1, characterized in that: The phosphorus in the first phosphorus / carbon composite material or the second phosphorus / carbon composite material includes at least one of red phosphorus, black phosphorus, yellow phosphorus, and purple phosphorus; the carbon includes at least one of hard carbon, amorphous carbon, graphene sheets, redox graphene sheets, biomass carbon, and carbon nanotubes.
7. The preparation method according to claim 1, characterized in that: The mass content of carbon in the first phosphorus / carbon composite material is 1-50%.
8. The preparation method according to claim 1, characterized in that: The mass content of carbon in the second phosphorus / carbon composite material is 1-24%.
9. The phosphorus negative electrode material prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Sodium-ion battery negative electrode, preparation method thereof and sodium-ion battery
CN116544352A
Electrode sodium pre-treatment method and sodium pre-treatment electrode
CN118431414A
Ultrathin composite foil and preparation method and application thereof
CN118849595A
Sodium-ion battery negative electrode sodium-pre-modification method for preparing electrode film based on dry method
WO2024001591A1